Resource management for construction an integrated approach - Canter, M. R. (Michael R.) (Macmillan building and surveying series, 1993)
This work offers a new approach to the management of resources within the construction industry, and with special reference to smaller construction companies. A systems approach, based on a case study, is adopted to describe how the basic production resources are planned for, monitored and managed. Each resource is considered in detail, highlighting its associated problems for management, the aim being to develop a structured approach to the management of each resource within an overall integrated framework. The early chapters examine the problems of resource control - they describe the economic, financial, social and legal constraints under which management are taken. Subsequent chapters deal with manpower, materials, plant and subcontracting. Then come several chapters that examine costs from the viewpoint of classification, monitoring and control. The closing chapters discuss resource cost management and cashflow, culminating in a final chapter that demonstrates how an integrated system of cost and cashflow management may be operated. The book should appeal to both students and practitioners, since it aims to bridge the gap between academic theory and practical reality. Managers should find the systems descriptions provide a useful reference for designing their own management framework. Students of construction management should appreciate the structured approach to planning and control.